Case Report: Reversible Hyperglycemia Following Rapamycin Treatment for Atypical Choroid Plexus Papilloma in an Infant - Liu, Jiale; Luo, Minjie; Lv, Siyuan; Tao, Shaohua; Wu, Zhu; Yu, Lihua; Lin, Danna; Huang, Lulu; Wu, Li; Liao, Xu; Zi, Juan; Lai, Xiaorong; et al. (Frontiers in Endocrinology, 2022)
In this study, atypical choroid plexus papilloma was treated with high-dose rapamycin for 17 days preoperatively in an infant. Rapamycin significantly reduced the blood supply to the tumor while reducing the tumor volume, and most of the tumor was resected successfully. However, the infant developed hyperglycemia related to the rapamycin dose, which was effectively controlled by adjusting the dose and applying insulin.